Preparing students for disasters: Integrating disaster risk reduction in the civil welfare course - Penullar, Neil Oliver T. (Animo Repository, 2014)
The massive loss of life and property caused by Typhoon Yolanda ('Haiyan') in the Philippines revealed the need for heightened disaster awareness and preparedness in the country. Most school-based disaster education initiatives, however, focused only at the elementary and secondary levels, respectively. The purpose of this study is to seek the most appropriate and effective method of integrating Disaster Risk Reduction in the curriculum of De La Salle University's Civic Welfare Training Service (CWTS). Best practices in DRR education were compared with survey results to identify outcomes and topics for inclusion in ten classroom sessions of the program. A lesson plan was developed for one of these sessions and was pilot-run for sixteen students. Participants exemplified increased understanding of basic DRR concepts as a result of the session.